2015
DOI: 10.1111/ene.12788
|View full text |Cite
|
Sign up to set email alerts
|

Low 25‐hydroxyvitamin D, but not the bioavailable fraction of 25‐hydroxyvitamin D, is a risk factor for multiple sclerosis

Abstract: Lower 25(OH)D3 levels already in the earliest phase of disease and in clinically hardly affected patients suggest that low 25(OH)D3 levels are rather a risk factor for than a consequence of MS. Nevertheless, because bioavailable vitamin D levels did not differ between the two groups, the mechanism underlying the association of 25(OH)D3 and MS does not appear to be related to reduced bioavailability of vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 33 publications
5
24
1
Order By: Relevance
“…In this cohort, VD deficiency showed an inverse association with measures of disability and was furthermore linked to a higher T2w lesion count but was not associated with T2 lesion volume, total brain volume as well as gray and white matter volumes. A high prevalence of VD deficiency in MS patients has been demonstrated in other studies: In an earlier study on a different patient cohort, we reported VD deficiency already in very early phases of MS (5). A cross-sectional study of 50 RRMS patients revealed a VD deficiency with a mean of 22.3 ng/ml /ml (42).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In this cohort, VD deficiency showed an inverse association with measures of disability and was furthermore linked to a higher T2w lesion count but was not associated with T2 lesion volume, total brain volume as well as gray and white matter volumes. A high prevalence of VD deficiency in MS patients has been demonstrated in other studies: In an earlier study on a different patient cohort, we reported VD deficiency already in very early phases of MS (5). A cross-sectional study of 50 RRMS patients revealed a VD deficiency with a mean of 22.3 ng/ml /ml (42).…”
Section: Discussionsupporting
confidence: 71%
“…The exact cause of multiple sclerosis (MS), a chronic inflammatory and neurodegenerative autoimmune disease of the central nervous system (1) is unknown. However, several environmental and genetic factors have been associated with MS pathogenesis, among them are vitamin D (VD) serum levels (2)(3)(4)(5), vitamin D receptor polymorphisms (VDP) (6)(7)(8)(9)(10), and sunlight exposure (11,12). In fact, increasing evidence suggests that VD deficiency may affect disease progression and outcome in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Low 25(OH)D serum levels have been associated with high risk of multiple sclerosis [26]. Free and bioavailable vitamin D did not differ between multiple sclerosis patients and their healthy controls [27]. In pediatric patients with chronic kidney disease, both free and bioavailable vitamin D were significantly lower than in healthy controls [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, its contribution to MS susceptibility is yet to be established, as studies inspecting this contribution have reported inconsistent results. The serum levels of DBP and calcitriol do not differ between patients and healthy controls, thus denying serum levels of bioavailable metabolite of vitamin D as a risk factor for MS. 19 Another study, denied the association between DBP serum levels and MS susceptibility/activity, as no differences were observed in DBP concentrations among subjects (RRMS patients in relapse/remission phase) and healthy controls. 20 Yet another study has reported DBP in MS patients to be of a higher serum level compared with healthy controls.…”
Section: Cyp24a1 Cyp27b1 Dbp and Vdr Genesmentioning
confidence: 99%